Coefficients Estimates for New Subclasses of Bi-univalent Functions Using Convolution Operator - Abdul-Rahman, Asmaa KH.; Al-Khafaji, Thamer Khalil MS.; Majed, Lieth A. (Iraqi Journal of Science, 2024)
We offered and suggested some classes N_(Ω,b,α,γ)^(μ,δ) (ψ,τ,φ) and C_(Ω,b,α,γ)^(μ,δ) (τ,a,ψ,φ) of bi-univalent functions in the unit disk υ, to apply the effects to the classes through convolution of the operators R_q^δ f(z) and I_(s,a,µ)^λ f(z). Which satisfies the condition quasi-subordination. We got estimates the first two Taylor-Maclaurin coefficients |a_2 | and |a_3 | by convolution of the operators R_q^δ f(z) and I_(s,a,µ)^λ f(z) .